Peran Teknologi Dalam Literasi Sains Siswa - Puput Aprilia Eka Sari; Sefti Eka Inggritiya; Moch. Dimas Reza; Rizal Wijayanto; I Ketut Mahardika; Singgih Bektiarso (Peneliti.net, 2023)
Linguistically, technology comes from the Greek, namely tekhnologia which is a combination of